Ideology and media framing: stigmatisation of LGBT in media coverage in Indonesia - M. Syam, Hamdani; Nur Anisah,; Saleh, Rahmat; Lingga, Murti Ali (Penerbit Universiti Kebangsaan Malaysia, 2021)
This essay analyzes how the ideology that is owned by the media influences the media's framing in reporting a reality. The framing dimension will always be related to the selection of issues, emphases, and projection on certain aspects of the issue. For this reason, this study will present the media cases of Republika.co.id and Tempo.co in informing LGBT reality. So, the reality of LGBT conveyed by Republika.co.id and Tempo.co cannot be seen separately, because it will be related to the interests that these two media outlets want to serve by reporting the reality. The analysis demonstrates that the reporting of Republika.co.id and Tempo.co on LGBT is influenced by each outlet's ideology. Republika.co.id, which embraces the ideology of nationalism and Islam, tends to report the rejection of LGBT presence in Indonesia. Republika.co.id provides a negative stigma against LGBT issues. It is considered that LGBT is a serious threat to the nation and state because behaviour is deemed not following religion, generally applicable social norms, and the laws of Indonesia. Tempo.co does not see LGBT as a serious problem for the Indonesian people. Tempo.co considers the behaviour and activities of LGBT people to be normal, which is part of human rights that must be respected by the Indonesian people.